1999
DOI: 10.1029/1999gl900437
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric water vapor amounts retrieved from GOME satellite data

Abstract: Abstract.A new method for the retrieval of global atmospheric vertical column amounts of water vapor from measurements of the Global Ozone Monitoring Experiment (GOME) is presented. The method is based on a modified Differential Optical Absorption Spectroscopy (DOAS) approach, taking into account the effects arising from strong wavelength dependent absorptions. In this paper the feasibility of this approach is demonstrated and first estimates on the retrieval precision and the accuracy of the H20 data product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
71
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 5 publications
0
71
0
Order By: Relevance
“…In particular it can observe the total atmospheric H 2 O column including the layers near the surface. GOME is now continuously operating for more than 7 years, thus these observations might be well suited for the investigation of trends of atmospheric trace gases like H 2 O. Atmospheric H 2 O has already been analysed from GOME observations and compared to independent data sets by different groups Maurellis et al, 2000;Casadio et al, 2000;Noël et al, 2000;2002, Lang et al, 2003 and reasonable agreement was found. However, these GOME H 2 O algorithms suffer from different shortcomings: a.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In particular it can observe the total atmospheric H 2 O column including the layers near the surface. GOME is now continuously operating for more than 7 years, thus these observations might be well suited for the investigation of trends of atmospheric trace gases like H 2 O. Atmospheric H 2 O has already been analysed from GOME observations and compared to independent data sets by different groups Maurellis et al, 2000;Casadio et al, 2000;Noël et al, 2000;2002, Lang et al, 2003 and reasonable agreement was found. However, these GOME H 2 O algorithms suffer from different shortcomings: a.…”
Section: Introductionmentioning
confidence: 84%
“…The earlier H 2 O algorithms did not take this cloud influence into account at all. First very promising attempts for a cloud correction using O 2 absorptions were undertaken by Noël et al (2000Noël et al ( , 2002 and Casadio et al (2000). However, usually the atmospheric profiles of O 2 with a scale height of ≈8 km and H 2 O are quite different (see Sect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaufman and Gao, 1992;Bauer and Schlüssel, 1993;Noël et al, 1999Noël et al, , 2004Maurellis et al, 2000;Wagner et al, 2006;Li et al, 2006;Deeter, 2007;Lang et al, 2007;Mieruch et al, 2008;Pougatchev et al, 2009). Within this framework, the European satelliteborne atmospheric sensor Global Ozone Monitoring Experiment 2 (GOME-2) aboard the Meteorological Operational satellite program (MetOp-A and MetOp-B) provides the potential for a detailed analysis of the global distribution of the atmospheric water vapour .…”
mentioning
confidence: 99%
“…In this context a new near real time retrieval algorithm was developed to demonstrate the capability of GO• to measure other trace gasses than ozone and nitrogen dioxide. Recently an attempt to retrieve water vapour concentration from GO• spectra has been presented, based on a modified DOAS (Differential Optical Absorption Spectroscopy) approach (Noel, 1999). In what follows an extremely simplified spectroscopic technique is proposed, which uses only raw uncalibrated spectra and geolocation information and requires only a few seconds computation time per orbit (including about 2000 single measurements).…”
Section: Introductionmentioning
confidence: 99%